1993
DOI: 10.1177/105345129302900107
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying Behavior Management Terminology

Abstract: Clarifies definitions and concepts associated with behavior management strategies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Teachers value different means of reaching these goals. Proponents of humane behavior management point to the advantages of reinforcement strategies, shaping, and response costs to make transitions efficient and reduce discipline problems (Justen & Howerton, 1993;Walker, Colvin, & Ramsey, 1995). In contrast, proponents of relational approaches to schooling, such as the RC approach, emphasize developing relationships with each child, spending time on community building, and setting up routines in the classroom to achieve these same goals (Battistich, Solomon, fim, Watson, & Schaps, 1995;Cohen, 2001;NEFC, 1997).…”
Section: Discipline and Behavior Managementmentioning
confidence: 99%
“…Teachers value different means of reaching these goals. Proponents of humane behavior management point to the advantages of reinforcement strategies, shaping, and response costs to make transitions efficient and reduce discipline problems (Justen & Howerton, 1993;Walker, Colvin, & Ramsey, 1995). In contrast, proponents of relational approaches to schooling, such as the RC approach, emphasize developing relationships with each child, spending time on community building, and setting up routines in the classroom to achieve these same goals (Battistich, Solomon, fim, Watson, & Schaps, 1995;Cohen, 2001;NEFC, 1997).…”
Section: Discipline and Behavior Managementmentioning
confidence: 99%
“…Previous research has indicated that teachers tend to implement positive reinforcement procedures over all others (Atici, 2007). A consistent finding has been that the teachers do not differentiate between negative reinforcement and punishment (Gaddis, 1980;Justen and Howerton, 1993;Maheady, Sacca, and Harper, 1982;Sidman, 2006). The principle difficulty was in the use of the term negative and punishment being used as synonyms.…”
Section: Discussionmentioning
confidence: 99%